2014
DOI: 10.4111/kju.2014.55.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Delayed Orchiopexies in a Korean Tertiary Care Hospital

Abstract: PurposeSince the 1990s, it has been well known that orchiopexies should be performed by no later than 2 years of age. Nevertheless, studies from other countries report a substantial number of delayed orchiopexies. On the basis of an analysis of a tertiary care hospital database, we aimed to investigate the incidence of delayed orchiopexies performed in patients after 5 years of age and to understand the causes of such delays and the possible consequences.Materials and MethodsWe retrospectively analyzed the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“… 7 Ahn et al, found that the reasons for delayed orchidopexy at a Korean tertiary care hospital were related to the parents of the child; parental requests for treatment of persistent retractile testis were delayed and approximately 15% of orchidopexy procedures were not performed at the proper time. 8 Similar results were observed in Austria; despite knowledge of the best timing for surgical treatment by pediatricians, orchidopexy was performed later than recommended. 9 In Saudi Arabia, it was observed that diagnosis and surgery of undescended testis are performed in a timely manner for only approximately half of the total patients treated.…”
Section: Discussionsupporting
confidence: 58%
“… 7 Ahn et al, found that the reasons for delayed orchidopexy at a Korean tertiary care hospital were related to the parents of the child; parental requests for treatment of persistent retractile testis were delayed and approximately 15% of orchidopexy procedures were not performed at the proper time. 8 Similar results were observed in Austria; despite knowledge of the best timing for surgical treatment by pediatricians, orchidopexy was performed later than recommended. 9 In Saudi Arabia, it was observed that diagnosis and surgery of undescended testis are performed in a timely manner for only approximately half of the total patients treated.…”
Section: Discussionsupporting
confidence: 58%
“…Semen specimens were collected by masturbation and the semen analyzed for sperm concentration and percent motility using computer-assisted semen analysis (SAIS Plus; Medical Supply, Seoul, Korea). The normal values used here were based on the World Health Organization 2010 reference limits [ 6 ]. Azoospermia was defined as an absence of sperm in the semen, and asthenozoospermia was defined as a ratio of motile sperm to all sperm of under 40%.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of the rate of secondary ascended testis on the timing of orchidopexy could not be analyzed in our data as administrative claims data do not provide clinical information. In a study from Korea, acquired cryptorchidism was seen as a reason for orchidopexy after the age of 5 years in 13% of the cases [40]. A study from Denmark reported ascensus testis accounting for 58% of all cases of undescended testis at the age of 18 months and 69% after the age of 36 months [3].…”
Section: Strength and Limitationsmentioning
confidence: 99%